Entrepreneurs Can Know More Than They Can Tell: Conceptualizing and Measuring Tacit Entrepreneurial Knowledge - Wuytens, Nils; Schepers, Jelle; Vandekerkhof, Pieter; Voordeckers, Wim (Frontiers in Psychology, 2022)
Organizational knowledge components dominate research on tacit knowledge. In order to overcome this dominance, we introduce Tacit Entrepreneurial Knowledge (TEK). TEK is conceptualized as one’s experiential learning from past experiences and insights that result in tacit knowledge regarding entrepreneurship that is implicit, personal, and uncodified. For this study the situational judgment test (SJT) approach is adopted to overcome the common limitations in quantifying an individual’s tacit knowledge. The SJT is a scenario-based measurement instrument that allows us to quantify an individual’s TEK. The SJT is developed using three steps: first, scenarios were collected through interviews, followed by formulating responses to the scenarios, and finally, the effectiveness of the responses for each scenario was evaluated. The outcome of this research article is threefold; first, a comprehensive conceptualization of TEK, including delineation of its nomological network. Second, the development of a measurement instrument for TEK and subsequent scoring method. Finally, an antecedent-consequence model which includes potential contingencies associated with these relationships. In the debate on tacit knowledge, our measurement is innovative and relevant, as previous research failed to uncover an individual’s tacit knowledge in the context of entrepreneurship, despite its importance in various entrepreneurial processes. This study aspires to ignite research into TEK by demonstrating important research opportunities unlocked by our conceptualization and subsequent measurement, offering future researchers a wide range of avenues to uncover the black box of tacit knowledge in entrepreneurship.